2017
DOI: 10.1038/s41598-017-01420-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating VEGF and eNOS variations as predictors of outcome in metastatic colorectal cancer patients receiving bevacizumab

Abstract: Novel predictive biomarkers are needed to improve patient selection and optimize the use of bevacizumab (B) in metastatic colorectal cancer. We analyzed the potential of five circulating biomarkers to predict B efficacy and monitor response. Peripheral blood samples collected at baseline, at the first clinical evaluation and at progression were available for 129 patients enrolled in the prospective multicentric ITACa trial and randomized to receive FOLFOX4/FOLFIRI (CT) with (64 patients) or without B (65 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The fact that high baseline VEGF-A and PlGF levels in patients treated with placebo are associated with poor outcomes is supported by previous reports (42)(43)(44). High VEGF-A serum levels (>5.1 pg/mL) at baseline were associated with worse OS and PFS in patients with mCRC who received either mFOLFOX6 or FOLFIRI with first-line bevacizumab (44).…”
Section: Discussionmentioning
confidence: 63%
“…The fact that high baseline VEGF-A and PlGF levels in patients treated with placebo are associated with poor outcomes is supported by previous reports (42)(43)(44). High VEGF-A serum levels (>5.1 pg/mL) at baseline were associated with worse OS and PFS in patients with mCRC who received either mFOLFOX6 or FOLFIRI with first-line bevacizumab (44).…”
Section: Discussionmentioning
confidence: 63%
“…This was consistent with the observation that L-NIO (a NOS3 inhibitor) inhibited cell growth and angiogenesis in colorectal cancer, and the anti-tumour effect of E7080 (lenvatinib) could be increased after combination with L-NIO in colorectal cancer (31,32). Although the analyses of NOS3 expression from the current TCGA data was not statistically relevant to the prognosis in COAD patients, Marisi et al found that the NOS3 expression level affected the progression-free survival and overall survival (OS) of metastatic colorectal cancer patients (9). In PRAD, NOS3 expression was higher in tumour tissues, but did not signi cantly affect overall survival (stage data could not be accessed).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, L-NIO could promote the anti-tumour effect of lenvatinib (31,32). The NOS3 level was signi cantly correlated with outcomes of bevacizumab-based chemotherapy in COAD (9,35). Unfortunately, bevacizumab, L-NIO, and L-NAME were not included in the CTRP database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding corroborates our hypothesis that the removal of the primary tumor brings several theoretical advantages. Tumoral cells produce high quantities of vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF), which can also be found in the blood circulation (45). These growth factors could have a stimulatory action on the liver metastases, neutralizing the action of the biological chemotherapy.…”
Section: Discussionmentioning
confidence: 99%